Developing National Urban Policies. Ways Forward to Green and Smart Cities. - (:unkn) unknown (Springer, 2020)
This book discusses and analyzes past and ongoing national urban policy development efforts from around the globe, particularly those that can lead the way toward smart and green cities. In view of the adoption of the UN’s 2030 Agenda for Sustainable Development, especially the goal to have cities that are inclusive, safe, resilient and sustainable, urban policies that can help achieve this goal are urgently needed. The UN-Habitat (HABITAT III) puts national urban policies at the heart of implementing and rethinking the urban agenda, and identifies them as being integral to the equitable and sustainable development of nations. Against this background, this important book, which gathers contributions from academics, planners and urban specialists, reviews existing urban policies from developing and developed nations, discusses various countries’ smart and green urban policies, and outlines the way forward.
Keywords: Nachhaltige Stadtentwicklung; Smart City; Stadtentwicklungspolitik; Nachhaltigkeit; Inklusion; Öffentliche Sicherheit; Resilienz; Klimaanpassung; Stadtbegrünung; Stadtplanung; Internationaler Vergleich; Nationale Stadtentwicklungspolitik; Agenda 2030 für nachhaltige Entwicklung